ANALISIS PERFORMANCE TM2500 GAS TURBINE GENERATOR PACKAGE PLTG X PADA FACTORY TEST DAN SITE TEST - Mohammad Faizal; Bambang Teguh Prasetyo; Eriq Sulton Effendy (Bina Teknika, 2017)
Background of this research is to compare the performance of Gas Turbin Power Plant between site test and factory test to make sure that there are no damage on equipment that can cause the decrease of Gas Turbine Performance, and also known the best operation mode in plant.Performance of Gas Turbine Power Plant can be seen from several parameters such as temperature and pressure can be seen from Calculation to be discussed is the work of  compressor, turbine,combustion chamber work, the efficiency of the compressor and thermal efficiency of the cycle brayton effective .            The result of performance test show that Gas Turbine performance decrease from 9389,54BTU/kWH and 9409,83 BTU/kWH in factory test to 9944,58 BTU/kWH and 9919.97 BTU/kWH in site test. While the best operation mode occurs when operated on DOHR at 90 to 100% load. Performance of gas turbine is directly proportional to the load. When the load is low, the performance of gas turbine decrease, and when the load is high, the performance of gas turbine increase. This mean that there is a positive correlation between load changes on the performance of gas turbines.